The use of 4-methylbenzenesulfonate ionic liquid derivatives as environmentally friendly corrosion inhibitors for mild steel in hydrochloric acid - T. Nesane; S. S. Mnyakeni-Moleele; L. C. Murulana (The Southern African Institute of Mining and Metallurgy, 2021)
The effectiveness of two synthesized ionic liquids, 1-(benzyloxy)-1-oxopropan-2-aminium 4-methylbenzenesulfonate (1-BOPAMS) and 4-(benzyloxy)-4-oxobutan-1-aminium 4-methylbenzenesulfonate (4-BOBAMS), were evaluated for mild steel corrosion inhibition in 1.0 M hydro-chloric acid solution, using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), and gravimetric techniques. Organic moieties responsible for the adsorption process on mild steel surface were investigated using Fourier transform infrared spectroscopy (FTIR). Gravimetric analysis revealed that the inhibition efficiency of 1-BOPAMS and 4-BOBAMS increased with concentration, with maximum inhibition values of 90.32% and 97.91%, respectively, at the highest concentration of the inhibitors. Gibbs free energy (ΔG°ads) values indicated a strong interaction between the mild steel surface and the molecules of the ionic liquids, and that the adsorption process was spontaneous. These values also show that the inhibitive nature of ionic liquids against mild steel corrosion is caused by a mixedtype of adsorption film formed on the steel surface. The Langmuir adsorption isotherm was used to describe the adsorption of ionic liquid molecules onto the mild steel surface. Polarization curves showed that 1-BOPAMS and 4-BOBAMS have a similar effect on both the anodic and cathodic half-reactions, indicating that they prevent the dissolution of mild steel through both physical and chemical process. Nyquist plots were defined by incomplete semicircle capacitive loops, showing that the charge transfer mechanism controls the corrosion of mild steel in acidic solution.